The State of Vegetative Regulation in Patients with Ischemic Stroke in the Acute and Peracute Periods: an Observational Cohort Study - N. T. Chekeeva; S. G. Shleifer; E. V. Andrianova; A. T. Jusupova (Кубанский научный медицинский вестник, 2022)
Background. The high number of stroke cases is predetermined by risk factors, pathogenetic heterogeneity, genetic predisposition to the disease. Neurovascular changes can serve as a marker for the severity of the patient’s condition. By means of cardiointervalography, the reactions of the autonomic nervous system in patients with ischemic stroke were studied, depending on the territory of the cerebral infarction and its period. With a favorable outcome of the disease, the detected changes in regulatory mechanisms can be considered adaptive, while with fatal outcome — disadaptive. Objectives. Determination of the state of the autonomic nervous system by means of cardiointervalography in patients with stroke in various pools of blood supply.Methods. 52 patients with a verifi ed diagnosis of ischemic stroke in the acute and peracute periods were examined. All patients were divided into 3 groups. Group 1 — patients with ischemic stroke in the middle cerebral artery territory on the left. Group 2 — with ischemic stroke in the middle cerebral artery territory on the right. Group 3 — with ischemic stroke in the vertebrobasilar territory. Patients with a fatal outcome are separately described. The functional state of the autonomic nervous system was assessed by the method of mathematical analysis of heart rate variability according to R.M. Baevsky (1984). Cardiointervalography was performed in the morning on the 1st day from the onset of the stroke and on the 10th day.Results. The state of autonomic regulation in patients with ischemic stroke depends on the localization and size of the lesion. According to cardiointervalography, parasympathetic effects on the rhythm of the heart prevailed in patients with ischemic stroke in the middle cerebral artery territory on the left and in the vertebrobasilar territory in the peracute period, while the sympathetic one predominated in patients with ischemic stroke in the middle cerebral artery territory on the right. In the acute period, the general tendency for the increase in activity of the opposite part of the autonomic nervous system was observed.Conclusion. Statistically signifi cant changes in the indicators of the total power of the wave oscillation spectrum and the indicator of ultra-low-frequency waves in the peracute and acute periods of stroke in the examined patients indicate the importance of neurohumoral mechanisms of regulation in the dynamics of the pathological state